Project Leadership / Second Edition - Briner Wendy; Geddes Michael; Hastings Colin (Gower Publishing, 2001)
This is a book that you will start thinking about people, relationships and teams. Preface, Acknowledgements, Introduction: The Brave New World of Project Management, The Project Leader, What Makes a Good Project Leader?, The Project in the Organization, Preparing the Ground, Understanding the Big Picture, Managing the Sponsor, Scoping, Managing the Project, The Project Start-Up Process, ''Marketing'' to the Stakeholders, Keeping on Track, Handling Over and Winding Up, Action Summary, Index.